Probing initial polymer precursor solution used in poly(dimethylsiloxane) membrane preparation by HPLC-APCI-MS and ESI-MS. Issue 3 (17th December 2015) - Das, Arun Kumar; Singh, Puyam S.
Abstract : The compositional aspect of the initial precursor solution in terms of molecular mass is very important as it affects the final PDMS membrane structure. Abstract : The compositional aspect of the initial precursor solution in terms of molecular mass is very important as it affects the final PDMS membrane structure. Herein, analytical techniques such as electrospray ionization mass spectrometry (ESI-MS) and high performance liquid chromatography (HPLC) combined with atmospheric pressure chemical ionization (APCI) mass spectrometry [HPLC-APCI-MS] were used for characterization of dilute solutions of two commercial precursors used in the PDMS membrane preparation. The mass spectrometry results showed the presence of linear as well as cyclic macromolecular units ranging from degree of polymerization (DP) 3 to 39 in the polymer solution which indicated the polydisperse nature of the polymer. This implied that the mass spectrometry data of the dilute precursor solution are in the 200–3000 m / z range which agrees well with solution viscosity.